Acromioclavicular joint cyst formation in a patient with rotator cuff-tear arthropathy: a rare cause of shoulder discomfort. (27th September 2018) - Maziak, Nina; Plachel, Fabian; Scheibel, Markus; Moroder, Philipp
Abstract : We report a case of a 77-year-old man who presented to our shoulder department with a soft tissue mass on his right acromioclavicular (AC) joint. Previously attempted puncture aspiration had revealed serous fluid retention which recurred after each of several drainage attempts. Conventional radiography and MRI of the affected shoulder joint demonstrated a progressed cuff-tear arthropathy with an irreparable tear of the supraspinatus tendon, static superior migration of the humeral head, opening of the AC joint capsule and a superior joint-fluid 'eruption' and accumulation called 'Geyser sign'. Given that the patient's cuff-tear arthropathy was very well compensated, arthroscopic rotator cuff debridement and open cyst excision were performed. Closure of the superior aspect of the AC joint capsule was performed by the aid of a collagen matrix with additional closure of the deltotrapezial fascia. One year postoperatively, no cyst recurrence was noted.